2013
DOI: 10.2174/138945013804999007
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases: Drug Targets for Myocardial Infarction

Abstract: Myocardial infarction (MI) remains a major cause of morbidity and mortality worldwide. Rapid advances in the treatment of acute MI have significantly improved short-term outcomes in patient, due in large part to successes in preventing myocardial cell death and limiting infarct area during the time of ischemia and subsequent reperfusion. Matrix metalloproteases (MMPs) play key roles in post-MI cardiac remodeling and in the development of adverse outcomes. This review highlights the importance of MMPs in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 96 publications
(113 reference statements)
0
9
0
Order By: Relevance
“…MMP8 inhibition has been proposed as a potential therapeutic target for several diseases, including sepsis (8, 19, 21), inflammatory bowel disease (22), chronic obstructive pulmonary disease (23), cerebral ischemia (18), acute myocardial infarction (24), and acute lung injury (25). Success depends on target specificity of the compound.…”
Section: Discussionmentioning
confidence: 99%
“…MMP8 inhibition has been proposed as a potential therapeutic target for several diseases, including sepsis (8, 19, 21), inflammatory bowel disease (22), chronic obstructive pulmonary disease (23), cerebral ischemia (18), acute myocardial infarction (24), and acute lung injury (25). Success depends on target specificity of the compound.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil-derived MMP-9 exerts early effects in the MI setting by degrading ECM and facilitating macrophage cell infiltration into the infarct area (19,36). Macrophages are another rich source of MMP-9.…”
Section: Mmp-9 Expression In Post-mi Leukocytesmentioning
confidence: 99%
“…Proinflammatory M1 macrophages dominate at day 1 post-MI, whereas anti-inflammatory M2 macrophages dominate starting from day 3 (37). M1 macrophages contribute MMP-9 and stimulate ECM degradation, whereas M2 macrophages contribute growth factors that regulate fibroblast differentiation and stimulate ECM production and deposition to form the infarct scar (36). The transition toward an M1 or M2 state is based on the local tissue environment (38).…”
Section: Mmp-9 Expression In Post-mi Leukocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrix metalloproteinases (MMPs) are enzymes that play a key role in cardiac remodeling and the development of adverse consequences after MI [11,12]. Peterson and colleagues [13] reported that MMP inhibition attenuates LV remodeling and dysfunction in a rat model of progressive heart failure.…”
mentioning
confidence: 99%